2008
DOI: 10.1152/ajprenal.90291.2008
|View full text |Cite
|
Sign up to set email alerts
|

Reduced renal responses to nitric oxide synthase inhibition in mice lacking the gene for gp91phoxsubunit of NAD(P)H oxidase

Abstract: Ϫ activity in the kidney, responses to administration of the NO synthase inhibitor nitro-L-arginine methyl ester (L-NAME; 200 g ⅐ min Ϫ1 ⅐ kg body wt Ϫ1 ) were assessed in knockout mice the lacking NAD(P)H oxidase subunit gp91 phox (KO; n ϭ 10) and in wild-type (WT; n ϭ 10) mice. Renal blood flow (RBF) and glomerular filtration rate (GFR) were determined by PAH and inulin clearances, respectively. Baseline RBF was higher in KO compared with WT mice (5.8 Ϯ 0.5 vs. 4.5 Ϯ 0.3 ml ⅐ min Ϫ1 ⅐ g Ϫ1 ; P Ͻ 0.04) withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…These findings generally resemble those with acute systemic infusion of NOS inhibitors, as mentioned earlier (3,16,18). Previously, it had been demonstrated that a high-salt (8%) diet induced increases in the production of various inflammatory cytokines including TNF-␣ in Dahl saltsensitive rats (41).…”
supporting
confidence: 83%
See 3 more Smart Citations
“…These findings generally resemble those with acute systemic infusion of NOS inhibitors, as mentioned earlier (3,16,18). Previously, it had been demonstrated that a high-salt (8%) diet induced increases in the production of various inflammatory cytokines including TNF-␣ in Dahl saltsensitive rats (41).…”
supporting
confidence: 83%
“…A blockade of NO synthesis by L-NAME administration in experimental animals leads to development of an oxidative stress condition, as indicated by an associated increase in U Iso V in many previous experiments in vivo (16,22,31) and an increase in vascular O 2 Ϫ production in vitro (38). It was also suggested that the production of inflammatory molecules such as TNF-␣ may be induced by the condition of oxidative stress (34,44).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…134,135 OXIDATIVE STRESS AND HUMAN HYPERTENSION Almost all experimental models of hypertension show some form of oxidative excess including genetic forms (spontaneously hypertensive rats, stroke-prone spontaneously hypertensive rats), surgically induced (2K1C, aortic banding), endocrine-induced (Ang II, aldosterone, deoxycorticosterone acetate) and diet-induced hypertension (salt, fat). [21][22][23][136][137][138] Sources of ROS in experimental models include Noxes (Nox1, Nox2 and Nox4), xanthine oxidase, uncoupled nitric oxide synthase and mitochondrial oxidases. Mice deficient in ROSgenerating enzymes have lower blood pressure compared with wild-type counterparts, and Ang II infusion fails to induce hypertension in these mice.…”
Section: Ros and Vascular Biology In Hypertensionmentioning
confidence: 99%